The System of Inheritance Distribution in Dusun Pulau Community, Air Rami District: A Comparative Study of Pekal Bacakuk Kayu Customary Law and Islamic Law - Rocky Eric Prianto; Deyan Ajian Putra; Ghania Khalisa Ridev; Muhammad Azka Zidane (JURNAL HUKUM SEHASEN, 2026)
One of the common issues in contemporary society is the problem of inheritance distribution systems, which are influenced by legal pluralism, including customary law, Islamic law, and western law. These differing legal systems often lead to inconsistencies in inheritance practices within communities. This study aims to analyze the comparison between the inheritance distribution system under Pekal Bacakuk Kayu customary law and Islamic inheritance law in the Dusun Pulau community, Air Rami District. This research is an empirical legal study supported by a normative approach, with data collection conducted through interviews and literature review. The data were analyzed qualitatively using an inductive reasoning method. The results show that under Pekal Bacakuk Kayu customary law, the inheritance system follows a matrilineal pattern, where daughters are considered the primary or even sole heirs, while sons do not receive any inheritance rights. This system is based on social values, customs, and the function of property in maintaining family continuity. In contrast, Islamic inheritance law stipulates a proportional and clearly defined distribution, where male heirs receive twice the share of female heirs, reflecting their economic responsibilities. This difference indicates the existence of legal pluralism within society, resulting in differing concepts of justice between customary law and Islamic law. Therefore, efforts toward harmonization are necessary to create a fair inheritance system that aligns with societal values.